Judicial Independence at the Regional and Sub-Regional African Courts - Swart, Mia (Southern African Public Law, 2017)
Qualified and independent judges are essential for the legitimacy of the Courts. African regional courts will only contribute to the rule of law if the courts are legitimately composed. The purpose of this article is to consider whether judicial independence at the African regional and subregional courts has contributed t setting standards for the rule of law in Africa. The focus will be on the African Court of Human and People's Rights as well as the courts of the most prominent subregional communities. Because of the influence of the African Commission the composition of this body will also be considered.